The History and Preservation of the Cultural Heritage of the Suster Pontianak Junior High School as a Source for Learning History - Firmansyah, Andang; Alghifari, Muhammad Aqif; Salwa Wardina, Yastrid (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research aims to discuss the History and Preservation of the Cultural Heritage of SMP Suster Pontianak as a Source for Learning History. This study employs a qualitative research method with a historical approach, which includes topic selection, data source collection, source criticism, interpretation, and writing. The results of this research trace the historical development of educational institutions established by the Sisters of the SFIC Congregation (Sororum Fransciscallum ab Immaculata, Conception A Beata Matre Dei) in West Kalimantan, particularly the Pontianak Sister Junior High School. Starting with the arrival of five SFIC sisters in 1906, this institution has grown with a focus on service in the fields of health and education. The preservation of buildings while maintaining their historical value and original architecture can serve as a source for learning history. In addition, through interviews with the school principal, it was revealed that students are taught to preserve that cultural heritage.